Exploration of Sources of Genetic Resistance in Maize Genotypes Against Stem Borer (Chilopartellus (Swinhoe)) (Bangladesh Journal of Agricultural Research, 2022)
Fourteen different maize genotypes were screened for their relative resistance to maize stem borer Chilopartellus (Swinhoe) under glass house condition at National Maize Research Program, Rampur, Chitwan during two consecutive years 2018 and 2019. The design of the experiment was completely randomized design having 2 replications. The unit plot size was one row of one meter length with 50 cm row to row and 20 cm plant to plant spacing. Two second instar larva of C. partellus (Swinhoe) per plant were released two times, first at 8th leaves (vegetative) and second at 12th leaves (Before tasseling) stages. Insect damage parameters (IDPs) viz. dead heart percentage, damage % at vegetative and foliar stage, foliar injury rating (1-9) at vegetative and before tasseling stage, tunnel length (cm), exit hole number and yield per plot were recorded to study the germplasm susceptibility level. The result revealed that IDPs and yield varied significantly among the tested genotypes. Over the years, IDPs like dead heart percentage (5.17%), percent damage atpre-tasseling stage (10.6%), foliar injury level (2.25), tunnel length (10.15 cm) and exit holes (2.32) were found lower with high yield (2235 g/plot) in RML-95/ RML-96 followed by RML- 86/RML-96. Two pipeline maize hybrids RML-95/RML-96 and RML-86/RML- 96 with least damaged by maize stem borer in both years will be useful for maize stem borer resistance source.Bangladesh J. Agril. Res. 45(3): 293-301, September 2020